Morphology-oxygen evolution activity relationship of iridium(iv) oxide nanomaterials. (2nd February 2022) - Mohan, Swati; Gupta, Santosh K.; Mao, Yuanbing
Abstract : This work demonstrated shape tuning of IrO2 nanoparticles to nanocube and nanorods in molten salt and demonstrated the exemplary performance of IrO2 nanorods as an electrocatalyst for oxygen evolution reaction even surpassing commercial IrO2 . Abstract : Heterogeneous photocatalysis is a promising strategy for addressing the worldwide energy shortage and environmental pollution issues. Due to the dependence of catalytic properties on their composition, size and shape, rational design can improve the utilization efficiency and catalytic performance of iridium oxide for the oxygen evolution reaction. Here we have induced a cube to rod transition in nanostructured iridium oxide (NIO) by tuning the salt to precursor ratio in the molten salt synthesis (MSS) process. Furthermore, we have compared the electrocatalytic performance of these NIOs for the oxygen evolution reaction (OER) in acidic media with that of commercial IrO2 nanoparticles (NPs) and its annealed derivative in terms of specific capacitance, total charge, most accessible charge, electrochemically active surface area, and roughness factor. Our NIOs synthesized using the MSS process showed enhanced electrocatalytic OER activity in 0.5 M H2 SO4 media compared to the commercial IrO2 NPs before and after annealing. A facile single-step synthesis of the IrO2 nanocubes and nanorods has been demonstrated and an electrochemical investigation suggested that the IrO2 nanorods exhibit the highest catalytic activities among all NIOs due to their high electrochemically active surface area, low charge transfer coefficient, high current density, high electrochemical stability, high accessibility to active sites and low overpotential, while the annealed commercial IrO2 NPs showed the worst performance. Our studies show a simple, reliable and scalable synthesis method from iridium tetrachloride salt to make shape tunable electrocatalytic NIOs which possess enhanced OER activity compared to commercial samples in acidic media.